1988
DOI: 10.1093/infdis/158.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Field Trial of Oral Cholera Vaccines in Bangladesh: Results of One Year of Follow-Up

Abstract: We assessed the protective efficacy (PE) of three doses of B subunit-killed whole cell (BS-WC) and killed whole cell-only (WC) oral cholera vaccines in a randomized, double-blind trial among 62,285 children and women residing in rural Bangladesh. After one complete year of surveillance, 110 cases of cholera were detected in the placebo group, 52 in the WC group (PE, 53%; P less than .0001), and 41 in the BS-WC group (PE, 62%; P less than .0001). Protection was greater for BS-WC recipients than for WC recipient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
1
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(86 citation statements)
references
References 22 publications
1
82
1
2
Order By: Relevance
“…A highly plausible explanation for the drastic reduction in cholera cases in the Jakarta trial accompanied by a low-point estimate of vaccine efficacy came subsequently when Ali et al (37) reported a reanalysis of the first-year results of the large-scale randomized controlled field trial in Bangladesh that assessed the efficacy of three oral doses of the B subunit (BS)/inactivated wholecell cholera vaccine (the precursor of Dukoral) or whole-cell vaccine alone, versus placebo (38). This innovative reanalysis examined vaccine efficacy in relation to the proportion of the target population in a geographically separated baris (patrilineally related clusters of households) that was vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…A highly plausible explanation for the drastic reduction in cholera cases in the Jakarta trial accompanied by a low-point estimate of vaccine efficacy came subsequently when Ali et al (37) reported a reanalysis of the first-year results of the large-scale randomized controlled field trial in Bangladesh that assessed the efficacy of three oral doses of the B subunit (BS)/inactivated wholecell cholera vaccine (the precursor of Dukoral) or whole-cell vaccine alone, versus placebo (38). This innovative reanalysis examined vaccine efficacy in relation to the proportion of the target population in a geographically separated baris (patrilineally related clusters of households) that was vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fusions retained some toxicity (A.-M. Svennerholm, personal communication). The CT-B component of the currently licensed cholera vaccine contributes to its protection against LT-ETEC diarrhea (6)(7)(8). A CT-B-ST vaccine could accordingly give protection against both ETEC enterotoxins.…”
Section: St Vaccinologymentioning
confidence: 99%
“…Strains of the classical biotype, which had probably been responsible for most of the epidemic disease in the 19th century and much of the 20th century, were largely replaced as the predominant cause of epidemic cholera by strains of the El Tor biotype in most of the regions where cholera is endemic, beginning in 1961. However, the classical biotype strains reemerged as a predominant epidemic strain in parts of Bangladesh in 1982 (8,25) and coexisted with the El Tor strains, causing disease until 1993. A second new epidemic strain, carrying the O139 rather than the O1 antigen, emerged in southern Asia in 1992 (7,24).…”
mentioning
confidence: 99%